Becoming a fashion show as part of a fashion tour and a tourist attraction based on the use of a costume - Артеменко, М. П. (Art and Design, 2019)
The purpose of the study is to identify the peculiarities of the development of fashion shows as tourist attractions based on the use of costume, as well as the definition of their place among the components of the modern fashion tour. The study contains historiographical and systematic analysis of publications on selected topics, periodization of the fashion show as a recreational and tourist resource, depending on the stages of increasing the scale of the audience, as well as systematization of the components of the modern fashion tour. The analysis of publications, which considers the history of becoming a fashion show through the prism of increasing the tourist potential. As a result, the theoretical study revealed a close relationship between the fashion industry and the tourism industry, which manifests itself in the early stages of development. The summary of the analysis of the formation of a fashion show as a recreational and tourist resource is presented in the form of a chronological scheme, in which, over decades, fundamental differences in the presentation of a costume on the podium can be traced, as well as five stages of increasing the scale of the audience, which indirectly reflect the growth of tourist and recreational interest to this type of activities. In addition, the place of fashion show in the systematic list of components of modern fashion tours is determined, among which, in addition to fashion shows, there are proposals for the purchase of goods from well-known brands with special discounts, visiting costume exhibitions, workshops and salons of designers of clothing, leading educational institutions in fashion, etc. Thus, the costume and all stages of its design and presentation are the key conceptual links around which a number of fashionable recreational and tourist proposals are formed. The chronology of the formation of a fashion show as a recreational and tourist resource based on the use of the costume has been built and the stages of its development have been determined depending on the stages of increasing the scale of the audience. Reasonably leading the fashion show among the components of the events of a modern fashion tour. The obtained results determine the possibilities of a deeper understanding of the role of a suit and ways of presenting it on the podium in modern lists of recreational and tourist events, and can also be used in the training of design specialists, in teaching disciplines related to costume design and fashion history, and in the practical activities of designers, costume artists, tourism managers and the like.